REPRESENTASI NUANSA WARNA HOROR PSIKOLOGIS DALAM GAME “OMORI” - Linda Chikita; Dianing Ratri; Irfansyah Irfansyah (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2022)
The psychological horror game genre generally revolves around the use of black and white or monochrome colors to convey the mental condition of their characters, but not Omori. This game is dominated by the use of pastel colors and neon colors in environment so that it offers a unique experience compared to games with similar themes. This journal examines the use of color in using color psychology theory and horror psychology using visual content analysis methods to find out how the role of color nuances in building psychological horror effects. Based on the results of the analysis, the dominating mixture of colors that often appears is black-white and red which represents the theme of the Omori game about coping mechanisms of pain due to grief from the death of a loved one that lasts too long.